In Memoriam Paul-André Meyer - Séminaire de Probabilités XXXIX - Yor, Marc; Émery, Michel (Séminaire de Probabilités,, 2006)
The 39th volume of Séminaire de Probabilités is a tribute to the memory of Paul André Meyer. His life and achievements are recalled; homages are rendered by his friends and colleagues. This volume also contains mathematical contributions to classical and quantum stochastic calculus, the theory of processes, martingales and their applications to mathematical finance, Brownian motion. They provide an overview on the current trends of stochastic calculus.